What Drives Gen Z to Apply? an Exploration of Work Expectations, Social Media Use, and Organizational Attractiveness in Indonesia - Adhelia Juwita Chairunnisa; Arman Jaya; Ana Fitriana; Titik Rosnani; Yuliyanti Fahruna (Journal of Educational Management Research, 2026)
This study aims to examine the influence of work expectations on intention to apply among Generation Z in Indonesia, with a particular focus on the mediating roles of social media use and organizational attractiveness in the context of digital recruitment. A quantitative explanatory approach was employed using a cross-sectional survey of 231 Generation Z individuals preparing to enter the labor market, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that work expectations do not have a direct effect on intention to apply; however, they significantly influence both social media use and organizational attractiveness. Furthermore, social media use has a significant positive effect on intention to apply, whereas organizational attractiveness does not show a significant influence. Mediation analysis indicates that social media use fully mediates the relationship between work expectations and intention to apply, while organizational attractiveness does not act as a mediator. These results imply that social media serves as a critical mechanism in translating job seekers’ expectations into application intentions, highlighting the importance for organizations to optimize digital recruitment strategies through interactive, informative, and engaging social media content to effectively attract Generation Z talent.